Transient and Quasi-Steady-State Analytical Methods for Simulating a Vertical Gas Flow in a Landfill with Layered Municipal Solid Waste - Xun Wu; Jianyong Shi; Tao Zhang; Yuping Li; Shi Shu (Mathematics, 2022)
The exploration of gas pressure and its distribution in landfills is a principal concern for the design and management of municipal solid waste (MSW) landfills. A one-dimensional analytical model was proposed to simulate a vertical gas flow in a landfill with layered MSWs. The transient analytical solution was obtained by the method of superposition and eigenfunction expansion and verified by a semi-analytical solution and numerical simulation. According to the results of a parametric analysis by the transient analytical solution, a vertical gas flow in landfills can be simplified to a quasi-steady-state flow. A quasi-steady-state analytical solution for simulating a vertical gas flow in a landfill with layered MSW is proposed. The quasi-steady-state analytical solution showed good agreement with the transient solution. Both temporal and spatial variations of the gas generation rate in MSW landfills were considered in the transient and quasi-steady-state analytical methods. A comparison between the proposed quasi-steady-state solution and the previously described steady-state solution showed that using the average gas generation rate or the gas generation rate corresponding to the average age of the MSW layer in the steady-state solution resulted in an error in the estimation of the gas pressure in landfills. The proposed solutions are reliable and can provide a reference for the design, management, and subsequent restoration of landfills.